Management of Postsurgical Complication in Multiple Implant-Infected Postextraction Sites in the Lower Arch - Frank Mayta-Tovalino; José Rosas; Cesar Mauricio-Vilchez; Silvia Luza; Daniel Alvitez-Temoche; Franco Mauricio (International Journal of Dentistry)
Currently, dental implants are a very frequent therapeutic alternative for replacing missing teeth. However, they are not exempt from developing complications of infectious origin. Therefore, this case report describes a 67-year-old female patient presenting infectious complications caused by suture rupture. Surgery combined with therapeutic management with antibiotics was performed, allowing preservation of the osseointegration of the implants in the lower arch. Within the limitations of this study, it was shown that more research is needed to determine the success and survival of implants presenting complications due to infections during the osseointegration process.